Promoting safety participation through diversity and inclusion climates - Paolillo, A.; Silva, S. A.; Pasini, M. (International Journal of Workplace Health Management, 2016)
Purpose: The purpose of this paper is to investigate the impact of diversity climate and inclusion climate on safety participation behaviors through the mediating effect of the motivation to actively promote safety at work. Design/methodology/approach: Participants were 491 workers employed in four Italian metal-mechanical companies. They completed a paper questionnaire containing measures of psychological diversity climate, psychological inclusion climate, safety motivation participation and safety participation behaviors. Data were analyzed with structural equation modeling. Findings: Results showed that safety participation motivation fully mediates the relationship between diversity climate and safety participation behaviors, whereas it partially mediates the relationship between climate for inclusion and safety participation behaviors. Practical implications: The present findings can help managers to motivate employees in pursuing safety goals independently of compensation or obligation by creating an organization in which the main concern is caring for each other’s well-being. Originality/value: This is the first study which has empirically tested the relationships between diversity climate, inclusion climate and safety behaviors. It has extended previous research which simply tested the effects of objective types of diversity on safety performance.